Evolutionary origin of the amnioserosa in cyclorrhaphan flies correlates with spatial and temporal expression changes of zen - Rafiqi, Abdul Matteen; Lemke, Steffen; Stauber, Michael; Schmidt-Ott, Urs (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Higher cyclorrhaphan flies including Drosophila develop a single extraembryonic epithelium (amnioserosa), which closes the germband dorsally. In most other insects two extraembryonic epithelia, serosa and amnion, line the inner eggshell and the ventral germband, respectively. How the two extraembryonic epithelia evolved into one is unclear. Recent studies have shown that, in the flour beetle Tribolium and in the milkweed bug Oncopeltus, the homeobox gene zerknüllt (zen) controls the fusion of the amnion with the serosa before dorsal closure. To understand the origin of the amnioserosa in evolution, we examined the expression and function of zen in the extraembryonic tissue of lower Cyclorrhapha. We show that Megaselia abdita (Phoridae) and Episyrphus balteatus (Syrphidae) develop a serosa and a dorsal amnion, suggesting that a dorsal amnion preceded the origin of the amnioserosa in evolution. Using Krüppel (Kr) and pannier (pnr) homologues of Megaselia as markers for serosal and amniotic tissue, respectively, we show that after zen RNAi all extraembryonic tissue becomes indistinguishable from amniotic cells, like in Tribolium but unlike in Drosophila, in which zen controls all aspects of extraembryonic development. Compared with Megaselia and Episyrphus, zen expression in Drosophila is extended to cells that form the amnion in lower Cyclorrhapha and is down-regulated at the developmental stage, when serosa cells in lower Cyclorrhapha begin to expand. These expression differences between species with distinct extraembryonic tissue organizations and the conserved requirement of zen for serosa development suggest that the origin of an amnioserosa-like epithelium was accompanied by expression changes of zen.